Landsbygdsdöden - Lundgren, Anna Sofia (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2013)
What do people mean when they say that rural Sweden is dying? This article scrutinizes what happens when Swedish Norrlandic ‘rurality’ is articulated with ‘death’. Working from a perspective of discourse theory, statements of the death of rural areas can be said to comprise both unproblematised notions of the end of an era and politiziced notions of the unfairness of the situation, which in turn may strengthen rural identifications.